Denk mal - Geschichte - Derichs, Johannes; Intemann, Gabriele; Kiwitt, Holger; Machate, Christian; Pankratz, Wolfgang; Schröfel, Karin; Stiller, Eike (Schroedel, 2013)
Verlagsinfo: Passgenau zu den curricularen Vorgaben für die Oberschule in Niedersachsen